2020
DOI: 10.2147/cmar.s271910
|View full text |Cite
|
Sign up to set email alerts
|

<p>Knowledge, Attitudes, and Practices of Cancer Patients Towards COVID-19: A Cross-Sectional Study in Central Nepal</p>

Abstract: Introduction: Cancer patients are at higher risk of COVID-19 infection as they are highly immunocompromised. The patients' adherence to control measures is affected by their knowledge, attitudes, and practices (KAP) towards COVID-19. This study assesses the KAP towards COVID-19 among the admitted cancer patients in Nepal and is first of its kind. Patients and Methods: A cross-sectional study was conducted among the 224 admitted cancer patients in B.P. Koirala Memorial Cancer Hospital, Chitwan, Nepal, between A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
18
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 13 publications
4
18
1
Order By: Relevance
“…There was a significant variation in the knowledge of preventive measures for COVID-19 depending on the district patients came from. A similar study conducted by Sah et al 4 among cancer patients in Nepal reported higher level of awareness of COVID-19 among illiterate participants. We found a significant variation among the participants’ knowledge level based on their educational attainment.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…There was a significant variation in the knowledge of preventive measures for COVID-19 depending on the district patients came from. A similar study conducted by Sah et al 4 among cancer patients in Nepal reported higher level of awareness of COVID-19 among illiterate participants. We found a significant variation among the participants’ knowledge level based on their educational attainment.…”
Section: Discussionsupporting
confidence: 55%
“…The knowledge level was higher among participants with higher qualifications. 4 An online survey conducted in the Nepalese community reported similar findings of increased knowledge of COVID-19 among more educated participants. 5 Regarding the attitude of participants toward COVID-19, we studied various myths and misconceptions prevalent in the community.…”
Section: Discussionmentioning
confidence: 76%
“…In a similar study conducted during the same period in Nepal, more than 98% of cancer patients were found to be compliant with the recommended preventive behaviours, and 94.6% were familiar with the common symptoms of COVID-19 (fever, cough, sore throat and shortness of breath), despite low levels of formal education and literacy. 22 Better knowledge and practice regarding COVID-19 were observed in cancer patients from Nepal compared with Romania, but the sample of participants included was smaller (224 participants from only one cancer hospital). 22 …”
Section: Discussionmentioning
confidence: 95%
“… 22 Better knowledge and practice regarding COVID-19 were observed in cancer patients from Nepal compared with Romania, but the sample of participants included was smaller (224 participants from only one cancer hospital). 22 …”
Section: Discussionmentioning
confidence: 95%
“…The concerns and fears, the impact of knowledge, variation in adherence to precautionary measures, avoidance of medical care, preference for virtual visitation and other factors have been reported in different populations. Thus lessons learned from this study could be of benefit to the global oncology community [29][30][31][32][33].…”
Section: Discussionmentioning
confidence: 90%